مؤلّفات يوسف بن حسن بن عبد الهادي ومساهمته في حفظ التّراث الفكريّ Muʾallafāt Yūsuf b. Ḥasan b. ʿAbd al-Hādī wa-Musāhamatuhu fī Ḥifẓ al-Turāth al-Fikrī - Aljoumani, Said (Brill, 2021)
On the basis of a newly discovered manuscript this book offers the most comprehensive bibliography of the enormous output of the fifteenth-century scholar Ibn ʿAbd al-Hādī - enlarging our view of his scholarly contribution and correcting numerous mistakes in this regard. This book is thus essential reading for all those interested in the writerly world of Damascus and the scholarly world of the late fifteenth century, especially with regard to the Ḥanbalī tradition and ḥadīth scholarship. In particular, linking the titles of his books with the extant manuscripts in libraries around the world opens new perspectives to these scholarly worlds. At the same time this book offers a new framework to studying social history with reference to documents and the material culture of the book.. Readership: All interested in Islamic Studies and especially history of the book and history of libraries. The focus on the Ḥanbalī heritage will appeal in particular to those interested in Ḥanbalism.